Making the case for environmental markets - Toombs, Ted, speaker; Unidentified speaker (Colorado State University. Libraries, 2010)
For decades markets have been one of the most destructive forces encouraging the overuse and wasting of natural resources. But, markets also have the potential to help us conserve resources if we design them right. In my talk, I'll use personal examples to demonstrate the potential benefits of using markets to drive conservation as opposed to traditional conservation approaches. I'll encourage discussion and engagement from the audience.
Presented at the Fall 2010 Center for Collaborative Conservation (https://collaborativeconservation.org/) Seminar and Discussion Series, "Collaborative Conservation in Practice: Ecosystem Services and Environmental Markets", September 21, 2010, Colorado State University, Fort Collins, Colorado. This series focused on the role of payments for ecosystem services (PES) in collaborative conservation efforts across the Western U.S. and around the world.
Ted Toombs is an ecologist by training and has been at Environmental Defense Fund for seven years. During this time he has worked to design and implement cooperative conservation tools such as safe harbor agreements and farm bill conservation programs. Recently, he led the design of a unique, market-based conservation tool that is now being pilot tested for an endangered species in Utah. He is also working to develop other voluntary and regulatory tools to stimulate markets for carbon sequestration and biodiversity in the Rocky Mountain west.
Includes recorded speech and PowerPoint presentation.
Accessibility features: Unedited transcript.
Keywords: EDF; Environmental Defense Fund; environmental markets; conservation